Environmental Consequences of Rehabilitation of Residential Buildings in Turkey: A Case Study of Istanbul - Ceylan, Nurten; Çetiner, İkbal (Pergamon-Elsevier Science Ltd, The Boulevard, Langford Lane, Kidlington, Oxford Ox5 1Gb, England, 2013)
This paper explains a method developed to assess environmental performance achieved by rehabilitation of residential buildings in Turkey. Several measures focussing on a reduction in the heating demand were investigated such as replacement of window and insulation of different elements of building skin. The influence of several building characteristics was moreover examined such as window to wall ratio (WWR), orientation and building age. Another important aspect which affects environmental performance is climate. In the context of this method, rehabilitations were proposed for temperate-humid climates like Istanbul. According to the assessment results, an environmental performance is obtained for all proposed rehabilitations. When proposed rehabilitations are analysed separately, the environmental performance ratios resulting from the rehabilitations of exterior walls and projected floors, roof, window system, and floors above unheated spaces reduce respectively. WWR has the highest effect on the environmental performance ratios obtained by rehabilitations. The effects of building age and orientation are in negligible amounts when compared to that of WWR. In the future, these assessments should be carried out for different climatic regions of Turkey as well. This method can be used to assess existing and new buildings in terms of environmental impacts by architects, contractors, building owners or municipal authorities. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: environmental impact assessment; building element; LCA; Impact 2002; Turkey; life-cycle assessment; optimum insulation thickness; external walls; methodology; energy; emissions; benefits; impact; tools; çevresel etki değerlendirmesi; yapı öğesi; Türkiye; yaşam döngüsü değerlendirmesi; optimum izolasyon kalınlığı; dış duvarlar; metodoloji; enerji; emisyonlar; faydalar; darbe; araçlar